THE EFFECT OF PERIODIC FATIGUING ON SEED GROWTH AND SURVIVAL JURUNG FISH (Tor soro) - Huda. J, Mhd Aidil; Nisari, Tika; Rumondang, Anne; Khobir, Muhammad Latiful; Mahaji, Toga; Suriyadin, Adi (Jurnal Perikanan Unram, 2024)
Jurung fish is one of the endemic freshwater fish in the Central Tapanuli river which is often called Batak fish (Neolossochilus thienemanni). Periodic fasting can increase the growth rate of fish to the same level or even higher when compared to fish that are not fasted. This research aims to determine the repetition of the feeding cycle followed by constant feeding on feed consumption and feed performance, as well as determine the level of feed requirements for Jurung (Tor soro) fry after a period of 2-3 days. The information obtained includes absolute weight, absolute length and viability (SR) as well as water quality. This research was carried out at the Production Laboratory of the Matauli College of Fisheries and Maritime Affairs in July-September 2024. The method used was an experimental method with an experimental design using a Completely Randomized Design (CRD) with 4 treatments and 3 replications. The fish tested were Jurung fish fry measuring 3-5 cm. with an average duration of 1.60 ± 0.00 cm and an average weight of 2.16 ± 0.23 g. Feeding is given at 08.00-08.10, 12.00-12.10, and 16.00-16.10. The fish are kept at a stocking density of 15 fish. The results showed that the feeding approach had a large influence (P<0.05) on absolute length and absolute weight, but had no significant effect (P>0.05) on survival. Treatment P1 gave absolute weight results of 2.16 ± 0.23c, absolute length of 1.60 ± 0.00c and survival of up to 93.33% which was the highest of the treatments carried out